Il ruolo delle emozioni nell’esperienza estetica - Stefano Mastandrea (Rivista di Estetica, 2011)
The present work has the aim to understand the role of the emotions in the aesthetical experience. Most modern theories refer to a componential approach to emotion, indicating that an emotional event consists of several components: cognitive appraisal, physiological arousal, expression, action tendency and subjective feeling. This model is applied to the so called utilitarian emotions. Is that possible to adopt the model also to the aesthetic emotions? We will analyze every step of the componential approach trying to compare it with the process underling aesthetic emotion, highlighting similarities and differences.